The Instant Effects of Continuous Transcutaneous Auricular Vagus Nerve Stimulation at Acupoints on the Functional Connectivity of Amygdala in Migraine without Aura: A Preliminary Study. (10th December 2020) - Luo, Wenting; Zhang, Yue; Yan, Zhaoxian; Liu, Xian; Hou, Xiaoyan; Chen, Weicui; Ye, Yongsong; Li, Hui; Liu, Bo
Abstract : Background . A growing body of evidence suggests that both auricular acupuncture and transcutaneous auricular vagus nerve stimulation (taVNS) can induce antinociception and relieve symptoms of migraine. However, their instant effects and central treatment mechanism remain unclear. Many studies proved that the amygdalae play a vital role not only in emotion modulation but also in pain processing. In this study, we investigated the modulation effects of continuous taVNS at acupoints on the FC of the bilateral amygdalae in MwoA. Methods . Thirty episodic migraineurs were recruited for the single-blind, crossover functional magnetic resonance imaging (fMRI) study. Each participant attended two kinds of eight-minute stimulations, taVNS and sham-taVNS (staVNS), separated by seven days in random order. Finally, 27 of them were included in the analysis of seed-to-voxel FC with the left/right amygdala as seeds. Results . Compared with staVNS, the FC decreased during taVNS between the left amygdala and left middle frontal gyrus (MFG), left dorsolateral superior frontal gyrus, right supplementary motor area (SMA), bilateral paracentral lobules, bilateral postcingulum gyrus, and right frontal superior medial gyrus, so did the FC of the right amygdala and left MFG. A significant positive correlation was observed between the FC of the left amygdala and right SMA and the frequency/total time of migraine attacks during the preceding four weeks. Conclusion . Continuous taVNS at acupoints can modulate the FC between the bilateral amygdalae and pain-related brain regions in MwoA, involving the limbic system, default mode network, and pain matrix, with obvious differences between the left amygdala and the right amygdala. The taVNS may produce treatment effects by modulating the abnormal FC of the amygdala and pain networks, possibly having the same central mechanism as auricular acupuncture.